Evaluating methods for purifying cyanobacterial cultures by qPCR and high-throughput Illumina sequencing - Heck, Karina; Machineski, Gabriela Silva; Alvarenga, Danillo Oliveira; Marcal Vieira Vaz, Marcelo Gomes; Varani, Alessandro de Mello [UNESP]; Fiore, Marli Fatima (Elsevier B.V., 2016)
Cyanobacteria are commonly found in association with other microorganisms, which constitutes a great challenge during the isolation of cyanobacterial strains. Although several methods have been published for obtaining axenic cyanobacterial cultures, their efficiency is usually evaluated by observing the growth of non-cyanobacteria in culture media. In order to verify whether uncultured bacteria should be a concern during cyanobacterial isolation, this work aimed to detect by molecular methods sequences from cyanobacteria and other bacteria present before and after a technique for obtaining axenic cultures from plating and exposure of Fischerella sp. CENA161 akinetes to the Extran detergent and sodium hypochlorite. Solutions containing 0.5, 1, and 2% sodium hypochlorite were able to remove contaminant bacterial CFUs from the culture. However, qPCR pointed that the quantity of sequences amplified with universal bacteria primers was higher than the number of cyanobacteria-specific sequences before and after treatments. The presence of uncultured bacteria in post-hypochlorite cultures was confirmed by high-throughput Illumina sequencing. These results suggest that culturing may overlook the presence of uncultured bacteria associated to cyanobacterial strains and is not sufficient for monitoring the success of cyanobacterial isolation by itself. Molecular methods such as qPCR could be employed as an additional measure for evaluating axenity in cyanobacterial strains. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Akinetes; Axenic cultures; Fischerella; Metagenomics; Symbiosis